Pengaruh Kualitas Pelayanan Dan kepercayaan Terhadap Kepuasan Nasabah Di Bank BRI Unit Pakkat: Kualitas Pelayanan, Kepercayaan, Kepuasan Nasabah - Mahulae, Artamala; Sholikhah, Afifatus (TALI JAGAD JOURNAL, 2024)
The current condition of banking competition is getting tighter, so bank management needs to always be sensitive to changes, environmental developments that occur and make continuous improvements in performance in providing satisfactory services to customers. This study aims to analyze the influence of service and trust on customer satisfaction at Bank BRI Pakkat Unit partially and simultaneously. The sample in this study consisted of 100 customers of Bank Rakyat Indonesia. The analysis technique used is multiple linear regression with an analysis tool, namely SPSS Version 26.0. The results of this study partially show that service quality and trust have a significant positive effect on customer satisfaction at Bank BRI Pakkat Unit. Based on the results of simultaneous tests, it was found that service quality and trust had a significant positive effect on customer satisfaction at Bank BRI Pakkat Unit.